FORMULATION AND IN-VITRO EVALUATION OF GASTRO-RETENTIVE FLOATING TABLETS CONTAINING QUETIAPINE FUMARATE (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
The present study was focused on Gastro-retentive tablets of Quetiapine fumarate using hydrophilic polymers HPMC K 250 PH PRM, HPMC K 750 PH PRM and HPMC K 1500 pH PRM as release retarding agents. WSR 301 was chosen as resin, Sodium bicarbonate was used as effervescent agents. FTIR studies revealed that there is no interaction between the drug and polymers used for the formulation. The tablets were prepared by direct compression method and the release rate was found to decrease with proportional increase in the ratio of polymer to drug. Quetiapine fumarate has good water solubility and is absorbed well from stomach and therefore is a very good drug to be formulated into gastro retentive floating dosage form. In-vitro release profile of Quetiapine fumarate and marketed product when compared, the optimized formulation F19 showed drug release of 98.61% within 24 h whereas 96.78% of the drug was released from the marketed product within 1h. The major mechanism of drug release follows zero order kinetics and non fickian transport by coupled diffusion and erosion. Such a formulation of Quetiapine fumarate with extended drug release over 24 hours probably is the best formulation for the treatment of Schizophrenia with only one oral tablet a day thus minimizing the side effects with low drug dose. The optimized formulation remained stable when subjected to accelerated stability studies.